THE ADMISSIBILITY OF EARTH OBSERVATION DATA IN LEGAL PROCEEDINGS: A CLOSER LOOK TOWARDS DATA IMAGING - Muhammad, Alif Nurfakhri (UI Scholars Hub, 2021)
Space capabilities utilization, specifically Earth observation capabilities is not just limited to environmental protection and disaster mitigation, as was shown in the UN Principles on Remote Sensing. It can also be used to support law enforcement and legal proceedings in court. However, the technology of Earth observation is very complex and the process from primary earth observation data to analyzed information requires a degree of manipulation to create comprehensive data. Because of this, there is an issue of admissibility of Earth observation data in court. This article would like to answer the fundamental question on how can this data be admissible, beginning with the procedure to obtain it and to ensure the authenticity of the data, and finds that there are methods of Data Imaging and Digital Audit that may ensure its authenticity. It will also find that obtaining this data for evidence requires a process of special agreement that needs to be looked at more in the future.